Tulipa kosovarica (Liliaceae), a new species of tulip from Kosovo - Shuka, Lulëzim; Tan, Kit; Krasniqi, Elez (Phytotaxa, 2012)
Tulipa kosovarica (Liliaceae) is illustrated and described as a new species from a serpentine area in Rahoveci province, southwestern Kosovo. It is related to T. serbica from northern Kosovo and had previously been confused with T. scardica from (F.Y.R.) Macedonia and southern Kosovo, all found on serpentine soils.  Comparison is made with the recently described T. albanica from northeastern Albania. Ecological data for T. kosovarica is presented in detail and the distribution of all four species in the Balkan Peninsula is mapped.